Analisis Faktor Yang Berhubungan Dengan Peningkatan Insiden Persalinan Sectio Caesarea - Yunita Anggriani; Ria Putriana M.Pasau; Frety Carolis (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The global and national rates of cesarean section (CS) deliveries continue to show an increasing trend, including in Lampung Province. This study aims to analyze the factors associated with the increased incidence of CS deliveries at Griya Medika Dompet Dhuafa Hospital. An analytical quantitative design with a cross-sectional approach. The study population consisted of all mothers who gave birth during the period of January–June 2025. The sample was determined using the Slovin formula, yielding 240 medical records selected through simple random sampling. The independent variables included maternal age, educational background, obstetric history, and medical indications, while the dependent variable was CS delivery. The study was conducted from July to August 2025. Data were analyzed using univariate and bivariate methods with the Chi-Square test. The results showed that most respondents underwent CS delivery (95%). Maternal characteristics included non-risk age (73.8%), secondary education (38.3%), multiparity (54.2%), and the most common medical indication was fetal indication (55.4%). Bivariate analysis indicated no significant relationship between maternal age (p=0.519), educational background (p=0.509), and obstetric history (p=0.694) with CS delivery. Conversely, there was a significant association between medical indications and CS delivery (p=0.041). It was concluded that the increasing rate of CS deliveries is predominantly influenced by medical indications, particularly fetal indications. Therefore, it is recommended that health workers enhance early detection of pregnancy and childbirth risks and strengthen educational efforts for pregnant women as preventive measures to reduce the incidence of CS